Preparation and properties of poly(vinylidene fluoride) nanocomposites blended with graphene oxide coated silica hybrids - Q. Fu; J. C. Wang; P. Chen; L. Chen; K. Wang; H. Deng; F. Chen; Q. Zhang (eXPRESS Polymer Letters)
Graphene oxide coated silica hybirds (SiO2-GO) were fabricated through electrostatic assembly in this work, then blended with poly(vinylidene fluoride) (PVDF) by solution mixing to make PVDF nanocomposites. The interfacial interaction was investigated by scanning electron microscopy (SEM), polarized optical microscopy (POM) and Fourier transform infrared spectroscopy (FTIR). The results showed that the interfacial interaction was enhanced by adding of SiO2-GO and strong hydrogen bonds were observed. The as-made nanocomposites were investigated using standard tensile test and dynamic mechanical analysis (DMA) measurements, mechanical properties of PVDF with SiO2-GO hybrids showed limited improvement.